BUSINESS ADMINISTRATION STRATEGY, GREEN HUMAN CAPITAL, AND FINANCIAL ENTREPRENEURSHIP AS DRIVERS OF THE CIRCULAR BUSINESS MODEL - Amelia Setyawati; Rayyan Sugangga; Djoewita; Faisal Sugangga; Faizal Zulkifli (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue The growing global awareness of economic and environmental sustainability demands a transformation from linear business models to circular business models. However, at the local level such as in Malang City the implementation of this concept remains limited due to weak business administration systems, low green human capital competencies, and limited access to sustainable financing. Purpose: This study aims to analyze how business administration strategies, green human capital, and financial entrepreneurship function as key drivers of the circular business model in Malang City. Novelty: The novelty of this research lies in the integration of these three factors into a single conceptual framework that explains the dynamics of building a sustainable business ecosystem within the context of urban MSMEs. Research Methods: This study employs a qualitative approach through in-depth interviews with MSME actors, government officials, and financial institutions. Results: The findings indicate that the synergy between administrative efficiency, green human capital competencies, and financial innovation can strengthen circular business practices.. Research Contributions: This research contributes by proposing the “Integrative Circular Business Drivers” conceptual model, which broadens the theoretical perspective on sustainability and provides strategic direction for strengthening the green economy at the local level